Absence of detectable yield penalty associated with insensitivity to Pleosporales necrotrophic effectors in wheat grown in the West Australian wheat belt - Oliver, Richard; Lichtenzveig, Judith; Tan, Kar-Chun; Waters, O.; Rybak, K.; Lawrence, J.; Friesen, T.; Burgess, P. (Wiley-Blackwell, 2014)
Genetic disease resistance is widely assumed, and occasionally proven, to cause host yield or fitness penalties due to inappropriate activation of defence response mechanisms or diversion of resources to surplus preformed defences. The study of resistance gene trade-offs has so far been restricted to biotrophic pathogens. In some Pleosporales necrotrophic interactions, quantitative resistance is positively associated with insensitivity to effectors. Host lines that differ in sensitivity can easily be identified amongst current cultivars and advanced breeding lines. Large wheat cultivar trials were used to test whether lines sensitive or insensitive to three necrotrophic effectors from Pyrenophora tritici-repentis and Parastagonospora nodorum differed in yield when subjected to natural disease and stress pressures in the West Australian wheat belt. There was no significant yield penalty associated with insensitivity to the fungal effectors ToxA, SnTox1 and SnTox3. Some yield gains were associated with insensitivity and some of these gains could be attributed to increased disease resistance. It is concluded that insensitivity to these effectors does not render such plants more vulnerable to any relevant biotic or abiotic stress present in these trials. These results suggest that the elimination of sensitivity alleles for necrotrophic effectors is a safe and facile strategy for improving disease resistance whilst maintaining or improving other desirable traits.